Narratives of childhood domestic violence: epistemic justice, young women and transitions to young adulthood - Frances, Tanya (Women and psychology, 2025)
"Narratives of Childhood Domestic Violence explores young women's accounts of transitions to young adulthood after domestic abuse in childhood, from a psychological perspective. The book centres a dialogue about epistemic justice and how experiences of violence that are marginal, marginalised, and less easily understood through dominant discourses, can be listened to and heard. Taking a critical feminist psychological approach, Frances examines gendered and socio-culturally located narrative practices, arguing that narratives about change and transition in young adulthood after childhood domestic violence both re-inscribe societal narratives that can be constraining, as well as present stories of resistance and hope. The book draws attention to the difficulties of being heard and understood when articulating an experience that sits in tension with normative expectations and trajectories for families and children growing up within them. It also examines how tensions in storytelling practices are articulated in creative, nuanced and diverse ways. Frances ends the book by offering considerations for theory, research, and practice, including practical implications and interventions and recommendations for policy. This is an essential resource for academics and students interested in violence against women, feminist psychology, childhood abuse, and concerns around epistemic justice, as well as professionals in counselling, social work, charity work, law and policy making"-- Provided by publisher